On the Mechanism of the Reactivity of 1,3-Dialkylimidazolium Salts Under Basic to Acidic Conditions: A Combined Kinetic and Computational Study - Mera-Adasme, R (Wiley-VCH Verlag, 2018)
Comprehensive spectroscopic kinetic studies illustrate an alternative mechanism for the traditional free-carbene intermediated H/D exchange reaction of 1,3-dialkylimidazolium salts under neutral (D2O) and acidic conditions (DCl/D2O 35 wt % solution). The deuteration of high purity [bmim]Cl in D2O is studied at different temperatures, in absence of catalyst or impurities, to yield an activation energy. DFT transition-state modelling, of a small water cluster and [bmim] cation, also yields an activation energy which strongly supports the proposed mechanism. The presence of basic impurities are shown to significantly enhance the exchange reaction, which brings into question the need for further analysis of technical purities of ionic liquids and the implications for a wide range of chemical reactions in such media. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim